2019
DOI: 10.1177/2325967119837940
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors and Duration to Return to Sport After Isolated Meniscectomy

Abstract: Background: Return to sport (RTS) after meniscectomy is an important metric for young, active patients. However, the impact of the duration from surgery to RTS on clinical outcomes is not fully understood and is not reflected in outcome scores. Purpose: To establish when patients RTS after meniscectomy and to determine predictive measures for the ability to return to their preinjury activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…In the current study, we included 204 nonathletes. The mean time to RTA was 3.3 months, which was longer than those reported by Agarwalla et al 2 (2 months) and Lee et al 19 (7-9 weeks). This difference may be explained by the fact that rehabilitation centers are not as common in China as in Western countries; thus, when patients have knee-related symptoms, they are less likely to ask physical therapists for help, which may hinder the rehabilitation process.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In the current study, we included 204 nonathletes. The mean time to RTA was 3.3 months, which was longer than those reported by Agarwalla et al 2 (2 months) and Lee et al 19 (7-9 weeks). This difference may be explained by the fact that rehabilitation centers are not as common in China as in Western countries; thus, when patients have knee-related symptoms, they are less likely to ask physical therapists for help, which may hinder the rehabilitation process.…”
Section: Discussioncontrasting
confidence: 52%
“…However, there are many more nonathletes with meniscal injuries than athletes. Agarwalla et al 2 included 94 nonathletes in their study and found that a higher preoperative KOOS was associated with an increased rate of return to sports. However, the small sample size of their study may have weakened its statistical power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Body mass index greater than 25, lateral meniscal tears, tear pattern, and concomitant knee instability have been associated with poorer postoperative outcomes in a general population. 1 , 8 , 23 , 26 , 31 To the best of the authors’ knowledge, there has been only 1 other report of factors associated with RTP specific to elite soccer athletes. 23 Despite the well-established prevalence of meniscal injuries in soccer players, 20 there remains a notable gap in the literature in regard to treatment of isolated meniscal tear without concomitant ligamentous injury.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the timing of return-to-play (RTP), previous investigations have demonstrated that athletes typically RTP 1 to 3 months after meniscectomy 1 , 14 , 23 and 4 to 6 months after meniscal repair. 2 , 22 However, only 2 of these aforementioned studies have specifically isolated elite soccer players in their analyses.…”
mentioning
confidence: 99%